Reviews of recent publications (Studies in 20th & 21st Century Literature, 2011)
Elisabeth Mermann-Jozwiak and Nancy Sullivan. Conversations with Mexican American Writers: Languages and Literatures in the Borderlands by Tanya González Barbara Mennel. The Representation of Masochism and Queer Desire in Film and Literature by Amy Gates-Young David Damrosch. How to Read World Literature by Lisabeth Hock Maria DiFrancesco. Feminine Agency and Transgression in Post-Franco Spain: Generational Becoming in the Narratives of Carme Riera, Cristina Fernández Cubas and Mercedes Abad by Maryanne L. Leone Jennifer Wawrzinek. Ambiguous Subjects: Dissolution and Metamorphosis in the Postmodern Sublime by Claudine Fisher Maria Cristina Fumagalli. Caribbean Perspectives on Modernity: Returning Medusa’s Gaze by Laurence M. Porter Macedonio Fernández. The Museum of Eterna’s Novel by Todd S. Garth Russell West-Pavlov. Space in Theory: Kristeva, Foucault, Deleuze by Zoe Petropoulou Maria Beville. Gothic-postmodernism: Voicing the Terrors of Postmodernity by Terri Engnoth Sharae Deckard. Paradise Discourse, Imperialism, and Globalization: Exploiting Eden by Miguel González-Abellás Sangeeta Ray. Gayatri Chakravorty Spivak: In Other Words by Cybelle H. McFadden
Keywords: Mexican American Writers; Borderlands; Representation of Masochism; Queer Desire; Masochism; Queer; How to Read World Literature; World Literature; Feminine Agency; Post-Franco Spain; Carme Riera; Cristina Fernández Cubas; Mercedes Abad; Ambiguous Subjects; Caribbean Perspectives on Modernity; Kristeva; Foucault; Deleuze; Gothic-postmodernism; Paradise Discourse; Imperialism; Globalization; Gayatri Chakravorty Spivak